ZAKAT INFAK DAN SEDEKAH DALAM HUKUM EKONOMI ISLAM - Latif, Abdul (Islamic Economics Journal, 2013)
This paper discusses the introduction of Zakat, Infaq, and Sadaqah in Islamic law, and Law No. 23 of 2011 on zakat. Zakat, Infaq and Sadaqah (ZIS) conical in one definition, that is to issue something. Zakat, Infaq and Sadaqah have a legal basis described in the verses of the Qur’an, hadith, and ijma’. Zakat is obligatory to pay it, while for Infak and Sadaqah is sunnah. At first the management of zakat regulated by law 38 of 1999, which was later found to be irrelevant, so that it is needed to make a change. The old law was replaced by the new law no. 23 of 2011 which regulates the management of zakat. Management of zakah stipulated in this Law includes planning, collecting, distribution and utilization of zakat. In addition, the establishment of BAZNAS as a nonstructural government agency is responsible to the president through the minister. In performing its duties, BAZNAS financed by the State Budget and Amil Rights. Likewise with BAZNAS located on the province also earn fees from Regional Budget and Amil Rights.